1984
DOI: 10.1016/0014-5793(84)80334-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of two DCCD‐binding components in the envelope membrane of H. halobium

Abstract: From labeling studies using [14C]DCCD, the presence of two distinct DCCD‐binding sites was proved in halobacterial membrane, whose binding constants are 0.03 and 0.08 nmol DCCD/mg envelope protein, respectively. HPLC and SDS—PAGE analysis revealed that the radioactivity bound to these sites migrated with apparent molecular masses of 45 and 10.2 kDa protein components, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Inhibitor studies also suggested a high degree of resemblance to V-ATPases (Hochstein and Lawson, 19931 Ihara et al, 1992). The existence of a DCCD-binding proteolipid has been demonstrated, but there have been contradictory reports on its apparent molecular mass: 9.7 kDa (Steinert et al, 1997), 14 kDa (Dane et al, 1992, or 42 kDa (Konishi and Murakami, 1984). The Halobacterium salinarum genome contains a sequence for a putative 8 kDa proteolipid DCCD-binding protein with two transmembrane helices .…”
Section: Dissimilatory Biochemical Pathwaysmentioning
confidence: 99%
“…Inhibitor studies also suggested a high degree of resemblance to V-ATPases (Hochstein and Lawson, 19931 Ihara et al, 1992). The existence of a DCCD-binding proteolipid has been demonstrated, but there have been contradictory reports on its apparent molecular mass: 9.7 kDa (Steinert et al, 1997), 14 kDa (Dane et al, 1992, or 42 kDa (Konishi and Murakami, 1984). The Halobacterium salinarum genome contains a sequence for a putative 8 kDa proteolipid DCCD-binding protein with two transmembrane helices .…”
Section: Dissimilatory Biochemical Pathwaysmentioning
confidence: 99%
“…Konishi and Murakami [21] reported that membraffes from H. halobium strain R1 contained two DCCD reactive components (M r = 10 000-12 000 and 45000-62000). They concluded that the smaller peptide was not the DCCD-binding proteolipid of F0F 1 since no radioactivity was extracted with chloroform-methanol from membranes labeled with 14C-DCCD.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies (5)(6)(7), it was found that DCCD inhibits two H + -translocating processes in the membrane vesicles from H. halobium R]Mi. One is a passive H + -influx blocked by low DCCD concentrations.…”
mentioning
confidence: 83%